The Therapeutic Potential of Medicinal Foods - Nelvana Ramalingum; M. Fawzi Mahomoodally (Advances in Pharmacological Sciences)
Pharmaceutical and nutritional sciences have recently witnessed a bloom in the scientific literature geared towards the use of food plants for their diversified health benefits and potential clinical applications. Health professionals now recognize that a synergism of drug therapy and nutrition might confer optimum outcomes in the fight against diseases. The prophylactic benefits of food plants are being investigated for potential use as novel medicinal remedies due to the presence of pharmacologically active compounds. Although the availability of scientific data is rapidly growing, there is still a paucity of updated compilation of data and concerns about the rationale of these health-foods still persist in the literature. This paper attempts to congregate the nutritional value, phytochemical composition, traditional uses, in vitro and in vivo studies of 10 common medicinal food plants used against chronic noncommunicable and infectious diseases. Food plants included were based on the criteria that they are consumed as a common food in a typical diet as either fruit or vegetable for their nutritive value but have also other parts which are in common use in folk medicine. The potential challenges of incorporating these medicinal foods in the diet which offers prospective opportunities for future drug development are also discussed.